Cultivating Antifragility and Competitiveness of Delima Cakery Sukabumi in the Digital Landscape: Marketing Practices Adapting to the Evolution of the Marketing Mix - Wahdiniwaty, Rahma; Syafei, M. Yani; Firmansyah, Deri; Azhari, Andressa Noviar; Aqsha, Muhammad Farhan (PT. Riset Press International, 2025)
Disruptive technology increasingly challenges the agility, alignment and ability of SMEs with a quick response in creating products to communicating them to customers through various marketing techniques and management that are increasingly developing in an effort to grow antifragility and business competitiveness. Implementation of P2M by offering training themes and Platform-based marketing practices by adopting the evolution of the 4P marketing mix model in line with the development of digital technology, where